Conferences of Minister Presidents of the German States in 1945—1947 as a Prerequisite for the Formation of the Federal Republic of Germany - I. D. Popov (Научный диалог, 2020)
The formation of the Minister Presidents of the German states conferences institution after the end of World War II until the end of 1947 is traced. For the fi time in Russian and post-Soviet historiography, the importance of interzonal meetings of heads of regional governments for the political development of Germany in the fi post-war years is shown. The results of the conferences in Stuttgart (February 6, April 3, 1946), Bremen (February 28 — March 1, 1946), Munich (June 6—7, 1947) and Wiesbaden (February 17, June 15—16, October 22, 1947 of the year) are considered. It is concluded that the experience of these meetings and, at the same time, the weak effectiveness of the inter-party dialogue persuaded the Western allies in December 1947 to choose the conference of Minister Presidents as the main negotiating platform with German politicians on the future constitution of West Germany. On the basis of published and archival documentary sources, the transformation of the conferences of Minister Presidents from consultative appendages of military administrations into an infl political structure claiming national representation is shown. At the same time, this infl according to the author of the article, was subject to serious restrictions from not only military administrations, but also party leaders.